Motion characteristics of youth women soccer matches: Female Athletes in Motion (FAiM) study - Vescovi, J. D. (International Journal of Sports Medicine, 2014)
This study determined the locomotor characteristics for youth female soccer matches. 89 female soccer players (U-15-U-17) were assessed during a youth national championship or a talent identification camp using a Global Positioning System. Positional and age-group comparisons of locomotor characteristics were made for complete games, each half, differences between halves as well as sprint profiles using an ANCOVA adjusting for the differences in game or half durations, respectively. Midfielders covered greater distances (8 449±170 m) than defenders (7 779±114 m), mostly from more low- (2 553±99 m vs. 2 151±66 m) and moderate-speed running (1 389±78 m vs. 1 142±52 m). Forwards had more sprint distances (275±42 m), sprints (15±2) and greater maximum speed (26.7±0.6 km/h) than midfielders (131±24 m, 8±1, 24.7±0.4 km/h, respectively). There was a tendency for increased distances within most velocity bands, workrate and sprints with increasing age. There was a greater increase in walking and jogging between the first and second half for forwards than defenders and midfielders. Youth female soccer players covered 6 500-9 000 m during matches with positional distinctions that are comparable to elite-standard women. These data provide novel insight into the physical demands of female youth soccer and should be used to establish appropriate age-group and positional strategies for training and development.